Point clouds with ground point classification and individual tree segmentation of 47 northern boreal forest and tundra sites from UAV-based lidar surveys in the eastern part of Alaska in 2023 - Kruse, Stefan; Enguehard, Léa; Juday, Glenn; Santosh, Panda; Badola, Anushree; Broers, Jakob; Farkas, Luca; Schladebach, Jacob; Hao, Kunyan; Jackisch, Robert; Döpper, Veronika; Heim, Birgit (PANGAEA, 2025)
This data set presents LiDAR 3D point clouds with centimetre precision, colored by a RGB camera module. It is a collection of processed point clouds that were collected by a UAV-based laser scanner (YellowScan Mapper). The region covered is part of the Boreal Forest and the Tundra-Taiga Ecotone (TTE). The aim is to map the forest structure and in particular to segment individual trees. This allows structural and biophysical information to be derived on forest condition, stand structure, topography, morphology, disturbance (wildfire, thaw slumps, wind events), thermokarst lakeshore interfaces, etc. The fieldwork was planned and carried out by researchers from the Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research (AWI) and the University of Alaska Fairbanks (UAF). It took place in the summer of 2023, from 20 June to 19 July. The study area covers boreal forests in different bio-climatic regions. The northernmost extent covers the tundra and open forested areas in the Brooks Range. We pre-selected a multitude of locations based on satellite data. Finally, it contains sites in Alaska Interior and the southern region of the boreal mainland of Alaska following generally all major roadways. At a multitude of sites, we pre-selected locations based on satellite data. At each site, transects at least 50 m wide and 500 m long were flown in a grid of parallel flight lines 20 m apart. At the ground level, one or, in rare cases, multiple 30-metre-diameter plots were inventoried as ground reference data. Before each flight, a differential GPS base station was set up to collect data for later positional correction. The recordings were made at an altitude of 70 m above ground liftoff at a speed of 5 m/s, as recommended by the manufacturer. The raw data processing steps involved correcting the flight trajectories in POSPAC PPTX, flight strip alignment in software YellowScan CloudStation, and point colorization with the RGB module picture data. The subsequent processing and metadata collection in PC2RCHIVE includes (i) ground classification, (ii) creating Digital Terrain Model (DTM), Digital Surface Model (DSM) and Canopy Height Model (CHM), (iii) tree segmentation, (iv) generating maps, and (v) adding user provided metadata and relevant information from the data processing are summarized in tables.
Keywords: Alaska; boreal forest; canopy cover; CHM; Drone; elevation model; Field measurements; GNSS; Individual Trees; Laser scanning; Lidar; permafrost; point clouds; Surface Elevation; thermokarst; topography; UAS; UAV; UAV data; Vegetation; wildfire